2018
DOI: 10.1029/2018gb005961
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Irrigation Practices Likely Mitigate Nitrous Oxide Emissions From California Cropland

Abstract: Crop production with intensive nitrogen (N) application is an important source of atmospheric nitrous oxide (N2O). However, there remains large uncertainty in quantifying cropland N2O emissions and their mitigation potential, especially in regions where cropping systems and farming management practices are highly diverse. Because N2O production in soils is tightly linked to N application rate and type, soil moisture, and oxygen status, improving irrigation is a potential strategy for N2O mitigation. We applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 48 publications
3
22
0
Order By: Relevance
“…The large difference found between irrigation systems was in the range of the results reported by Deng et al. (), who predicted a reduction of the 38% on soil N 2 O emissions for sprinkler‐irrigated maize systems compared with surface‐irrigated systems in Californian croplands. In two previous meta‐analysis for Mediterranean conditions, Cayuela et al.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…The large difference found between irrigation systems was in the range of the results reported by Deng et al. (), who predicted a reduction of the 38% on soil N 2 O emissions for sprinkler‐irrigated maize systems compared with surface‐irrigated systems in Californian croplands. In two previous meta‐analysis for Mediterranean conditions, Cayuela et al.…”
Section: Discussionsupporting
confidence: 61%
“…The large difference found between irrigation systems was in the range of the results reported by Deng et al (2018), who predicted a reduction of the 38% on soil N 2 O emissions for sprinkler-irrigated maize systems compared with surface-irrigated systems in Californian croplands. In two previous meta-analysis for Mediterranean conditions, Cayuela et al (2017) reported mean cumulative N 2 O emission values of 3.7 ± 3.3 kg N 2 O-N ha −1 for sprinkler irrigation systems, with a mean N application rate of 226 ± 75 kg N ha −1 , while Aguilera, Lassaletta, Sanz-Cobena, Garnier, and Vallejo (2013) estimated 4 ± 2.6 kg N 2 O-N ha −1 for furrow and sprinkler irrigation systems, with a mean N application rate of 137 kg N ha −1 .…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…The DNDC model used in this study had been calibrated and validated in a prior project with extensive N 2 O measurements in cropland and was found to perform well with an r 2 of 0.92 and a p value of <0.001 (Deng, Guo, et al, 2018;, indicating that the model we used adequately represented the biophysical conditions of agro-ecosystems in California. We have a much smaller data set for NO x emissions than for N 2 O, which was collected from major California's cropping systems over the past decade.…”
Section: Model Validation and Uncertaintiesmentioning
confidence: 85%